NILAI-NILAI BUDAYA DAN SOSIAL DALAM NASKAH DRAMA "BILA MALAM BERTAMBAH MALAM" KARYA PUTU WIJAYA - Arifan, Fari; Ifnaldi, Ifnaldi (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2023)
Abstract This research originates from the presence of cultural and social values ​​in Putu Wijaya's drama script Bila Malam Lagi Malam, which is very closely related to Balinese culture. , social issues and social status in the drama script When the Night Adds to the Night. This type of research is descriptive qualitative research. Data was taken from December 2022 to March 2023. The method used was reading drama scripts to be analyzed, analyzing cultural values, analyzing cultural values, and studying literary theory books on ethnography. The results of this study included (1) Cultural Values ​​of naming in the drama script Bila Malam Bertambo Malam. (2) Cultural value of each character's equipment, (3) Cultural value of the language used by each actor, (4) Cultural value of knowledge, (5) Human Relations with Culture. then the social values ​​in the drama script are (1) social issues based on human-human relations, (2) social status. the usual opening greeting given by Balinese people to someone they find. Keyword : Cultural and social values